Adherence to Guidelines for Screening and Medication Use: Mortality and Onset of Major Macrovascular Complications in Elderly Persons With Diabetes Mellitus - Yashkin, Arseniy P. (J Aging Health, 2016)
OBJECTIVE: The objective of this study is to investigate relationships between adherence to recommended screening and medication use and severe macrovascular complications and all-cause mortality among persons aged above 68 years with diabetes mellitus (DM). METHOD: Data came from a 5% Medicare claims sample of beneficiaries initially diagnosed with DM during 2006–2008; follow-up was up to 7 years. RESULTS: Adherence to screening guidelines led to reduced mortality—hazard ratio (HR) = 0.57, 95% confidence interval [CI] = [0.56, 0.58]; congestive heart failure [CHF], HR = 0.89, CI = [0.87, 0.91]; acute myocardial infarction [AMI], HR = 0.90, CI = [0.85, 0.95]; and stroke/transient ischemic attack [Stroke/TIA], HR = 0.92, CI = [0.87, 0.97]—during follow-up. Recommended medication use led to lower mortality: HR = 0.72, CI = [0.70, 0.73]; CHF, HR = 0.67, CI = [0.66, 0.69]; AMI, HR = 0.68, CI = [0.65, 0.71]; and Stroke/TIA, HR = 0.79, CI = [0.76, 0.83]. DISCUSSION: Elderly persons newly diagnosed with diabetes who adhered to recommended care experienced reduced risk of mortality and severe macrovascular complications.